Reviving Islamic Civilization in the Late Period of Abbasid: A Historical Analysis of the Madrasa al-Mustaná¹£iriyya - Agustono, Ihwan; Armayanto, Harda; Zain, Naura Safira Salsabila (University of Darussalam Gontor, Indonesia, 2024)
The spirit of education was renewed in the age of the Prophet Muhammad saw. through a talaqqÄ« method in the Majlis that used to be conducted in the mosque. This system then improved over time, particularly during the Abbasid era, when many educational institutes were built to preserve Islamic civilization. The Madrasa al-Mustaná¹£iriyya, constructed in 1234 AD during the reign of al-Mustaná¹£ir Billah, is one of the most renowned institutions. This madrasah is well-known for its complete system. This study aims to demonstrate the educational system's role in promoting civilization through the Madrasa al-Mustaná¹£iriyya, which will be discussed first on the social dimension in the era of al-Mustaná¹£ir Billah in order to comprehend the establishment of Madrasa Mustaná¹£iriyya, its educational system, and its collapse. Thus, the qualitative method will be employed in this work, along with a historical study approach gleaned from books, journals, and related publications. This research discovered that the purpose of Madrasa al-Mustaná¹£iriyya, which was established during the declining age of the Abbasid, was to restore the majesty of this dynasty. Despite the chaos, the Caliph successfully developed the spirit of science and education through the Madrasa al-Mustaná¹£iriyya. Furthermore, it provides facilities for academic support through the waqf system. Unfortunately, the Mongol invasion of Baghdad succeeded in destroying it.